Обставини, що виключають застосування кримінальної відповідальності та інших заходів кримінально-правового характеру - Ященко, А. М.; Yashchenko, A. M.; ORCID: http://orcid.org/0000-0003-3956-3487 (Вісник Кримінологічної асоціації України. - 2017. - № 1 (15). - С. 178-187, 2017)
На підставі аналізу приписів чинного Кримінального кодексу України, а також практики застосування його деяких положень виокремлено і вивчено регламентовані законом обставини, що виключають можливість застосування кримінальної відповідальності та інших заходів кримінально-правового характеру. Враховуючи отримані результати, сформульовано власні узагальнюючі висновки.

On the basis of the analysis of the regulations of the current Criminal Code of Ukraine and the practice of implementing its certain provisions the author has distinguished and analyzed regulated by the law circumstances precluding possibility of implementing criminal liability and other measures of criminal and legal nature, and on this basis has formulated own generalizing conclusions. It is noted that the circumstances, which preclude the application of criminal liability and other measures of criminal and legal nature, are instances regulated by the Criminal Code Ukraine, when, if they are present, it is impossible or not permitted to use criminal liability and some punitive and non-punitive measures of criminal and legal nature. It is emphasized that punitive measures of criminal and legal nature (various types of penalties) are always realized within such a complex social phenomenon as criminal liability. However, non-punitive, but compulsory or incentive measures or those that are based on humanistic principles and irrationality of implementing criminal proceedings, can find their realization both within the criminal liability (p. 4, 5 of the Art. 74, Articles 75, 79, 80, 81, 84, c. 2, p. 1 of the Art. 93, 96, Articles 967–969, p. 1 of the Art. 105) and out of its limits (the Art. 17, p. 1, 2 of the Art. 31, Articles 36–43, 45–49, c. 1, p. 1 of the Art. 93, the Art. 965, p. 1, 2 of the Art. 97). In this regard the author has noted that criminal liability is precluded under the current Criminal Code of Ukraine in cases if: 1) a person is in the condition of irresponsibility while committing socially dangerous offense under the Criminal Code of Ukraine (p. 2 of the Art. 19 of the Criminal Code of Ukraine); 2) committing an act similar to a criminal offense (Articles 36–43, p. 1 of the Art. 433); 3) there is the presence of voluntary refusal of committing criminal offense at the stages of previous criminal activities (the Art. 17, p. 1, 2 of the Art. 31 of the Criminal Code of Ukraine); 4) there is unconditional exemption from criminal liability (Articles 45, 46, 48, 49 of the Criminal Code of Ukraine); 5) implementing some requirements of the Constitution of Ukraine (p. 1 of the Art. 61, p. 1 of the Art. 63), which are reflected in p. 2 of the Art. 7, p. 2 of the Art. 385, p. 2 of the Art. 396 of the Criminal Code of Ukraine; 6) there is the presence of diplomatic immunity (p. 4 of the Art. 6 of the Criminal Code of Ukraine). The group of circumstances that preclude the applicability of certain measures of criminal and legal nature is represented by the circumstances precluding the possibility of using: 1) different types of punishments (p. 1 of the Art. 99, p. 3 of the Art. 56, p. 2 of the Art. 57, Art . 58, p. 1 of the Art. 98, p. 3 of the Art. 60, p. 3 of the Art. 61, p. 2 of the Art. 64 of the Criminal Code of Ukraine); 2) exemption from criminal liability under the norms set forth in the Section IX of the General Part of the Criminal Code of Ukraine (Articles 45, 46, 47, 48, p. 5 of the Art. 49 of the Criminal Code of Ukraine); 3) measures of criminal and legal nature to legal enteties (Articles 963–969 of the Criminal Code of Ukraine). It is separately noted that criminal liability and the possibility of applying exemption from criminal liability and punishment based on the requirements stipulated by p. 1 of the Art. 97 and p. 1 of the Art. 105 of the Criminal Code of Ukraine are excluded in case of committing socially dangerous acts by a person, who has not attained the age of criminal liability (p. 2 of the Art. 97 of the Criminal Code of Ukraine, Articles 498-502 of the Criminal Procedural Code of Ukraine).

На основании анализа предписаний действующего УК Украины, а также практики применения его отдельных положений, выделены и изучены регламентированные законом обстоятельства, исключающие возможность применения уголовной ответственности и иных мер уголовно-правового характера. Сформулированы собственные обобщающие выводы.
Circumstances precluding the implementation of criminal liability and other measures of criminal and legal nature
Обстоятельства, исключающие применение уголовной ответственности и иных мер уголовно-правового характера
Ященко, А. М. Обставини, що виключають застосування кримінальної відповідальності та інших заходів кримінально-правового характеру / Андрій Миколайович Ященко // Вісник Кримінологічної асоціації України. - 2017. - № 1 (15). - С. 178-187.
Yashchenko, A. M. (2017), “Circumstances precluding the implementation of criminal liability and other measures of criminal and legal nature” [Obstavyny, shcho vykliuchaiut zastosuvannia kryminalnoi vidpovidalnosti ta inshykh zakhodiv kryminalno-pravovoho kharakteru], Visnyk Kryminolohichnoi asotsiatsii Ukrainy, No. 1, pp. 178–187.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінальна відповідальність; заходи кримінально-правового характеру; обставини, що виключають кримінальну відповідальність; criminal liability; measures of criminal and legal nature; circumstances precluding criminal liability; уголовная ответственность; меры уголовно-правового характера; обстоятельства, исключающие уголовную ответственность